Drug-Induced Hypoglycemia in Neonates Born to Nondiabetic Women Treated with Medications during the Pregnancy or the Labor: A Systematic Review of the Literature - Maines, Evelina; Cardellini, Maria Chiara; Stringari, Giovanna; Leonardi, Letizia; Piccoli, Giovanni; Urru, Silvana Anna Maria; Maiorana, Arianna; Soffiati, Massimo; Franceschi, Roberto (American Journal of Perinatology, 2023)
The prompt identification of at-risk newborns for drug-induced hypoglycemia can minimize the risk for adverse side effects, inappropriate investigations, and considerable unnecessary costs. Existing literature discusses drug-induced hypoglycemia, but a systematic description of neonatal hypoglycemia induced or exacerbated by maternal medications is missing. We reviewed the association between neonatal hypoglycemia and maternal medications. We systematically searched the literature according to the PICOS model on drug-induced hypoglycemia in neonates born to nondiabetic women treated with medications during the pregnancy or the labor. The main outcomes of the review were: (1) prevalence of hypoglycemia, (2) risk factors and potential confounders, (3) time at onset and severity of hypoglycemia, (4) dose–response gradient, (5) metabolic features of hypoglycemia, (6) modalities to treat hypoglycemia, and (7) quality of the studies. We included 69 studies in this review and we identified 11 groups of maternal drugs related to neonatal hypoglycemia. Results were classified for each outcome. Our review aims at supporting clinicians in the identification of the newborn at risk for hypoglycemia and in the differential diagnosis of neonatal hypoglycemia. Further studies are necessary to assess the risk of neonatal hypoglycemia associated with common maternal medications.Key Points
Keywords: hypoglycemia; hyperinsulinism; perinatal; drug-induced hyperinsulinism; review